The Influence of Financial Literacy, Attitude toward Debt, Risk Perception, and Religiosity on Financial Satisfaction (Study on Bank Employees in East Java) - Wijayanti, Risna; Cahyaningtyas, Sindy Eka Yulianti; Ismayanti, Niken Wahyu (Journal of Entrepreneurship and Business, 2023)
Purpose: to contribute to further research on the conceptualization of financial satisfaction as a specific individual satisfaction domain based on subjective behavioral studies using a judgment approach. Financial Satisfaction is mostly studied based on standard economic theory which uses an objective approach in determining individual satisfaction with their financial conditions such as income, socio-demography, socio-capital, and socio-economy. This research examines several subjective variables in the form of judgment and examines the integrated relationship between these variables such as financial literacy, risk perception, attitudes toward debt, and religiosity. Method: The sample for this research was 100 bank employees in East Java using a random sampling method. The analysis technique used is SEM PLS. Result: The results show that financial literacy influences financial satisfaction among bank employees in East Java. Likewise, attitudes toward debt and religiosity also show an influence on financial satisfaction. Meanwhile, risk perception has no effect on financial satisfaction among bank employees in East Java.